Preventing Illegal Apple Imports: How BP Batam Contributes in Free Trade Zone - Silviani, Ninne Zahara; Febriyani, Emiliya; Hartono, Adi (Universitas Internasional Batam, 2023)
Batam is recognized as one of the regions within the Riau Islands Province designated as a Free Trade Zone (FTZ) in Indonesia due to its strategic positioning along international shipping routes. As a border region of Indonesia, it encounters challenges typical of other border areas, closely linked to issues of order, security, and national integrity. Moreover, within Batam, which serves as both a border area and an FTZ, a persistent issue revolves around the prevalence of illicit activities and the smuggling of foreign-origin products. The smuggling of electronic goods in Batam is driven by market demands beyond the city, seeking electronic items at comparatively lower prices than those in other regions. The lack of public awareness regarding the implications of purchasing illegal or smuggled goods constitutes a significant impediment to the eradication of illicit smuggling in Indonesia. This research employs the doctrinal or normative legal research method, utilizing secondary data obtained through a comprehensive review of literature such as books, journals, articles, and other relevant sources, including online resources. The choice of normative legal research method is justified by the research's objective, which aims to analyze the law from the perspectives of three fundamental legal values: justice, utility, and certainty. The findings of this research affirm that despite the legal regulations governing the criminal offense of smuggling and associated sanctions outlined in the legislation, the oversight implementation by BP Batam has not been entirely effective. This is evidenced by the continued occurrence of smuggling activities in Batam, attributed to various challenges encountered by BP Batam in their enforcement endeavors.